Genetic and antimicrobial resistance profiles of Salmonella spp. isolated from ducks along the slaughter line in southwestern China. (January 2020) - Han, Xinfeng; Peng, Junfeng; Guan, Xingai; Li, Jiakang; Huang, Xuelin; Liu, Shuliang; Wen, Yiping; Zhao, Qin; Huang, Xiaobo; Yan, Qigui; Huang, Yong; Cao, Sanjie; et al.
Abstract: The prevalence and diversity of Salmonella spp. was investigated along the duck slaughter line in Sichuan Province of China from May 2016 to July 2017. A total of 156 Salmonella isolates were recovered out of 523 samples with an overall prevalence of 27.3%, and high prevalence was observed in caecal samples (43.5%) and carcasses after defeathering (27.0%). Eleven different serotypes were confirmed, among which S . Indiana, S . Newlands and S . Newport were commonly observed serotypes. Resistance was most frequently observed against nalidixic acid (94.2%), followed by ampicillin (59.6%), tetracycline (51.3%) and trimethoprim/sulfisoxazole (46.2%) with a medium resistance level. Resistance to ciprofloxacin (27.6%), minocycline (20.5%) and kanamycin (19.2%) was less commonly detected. Among the Salmonella isolates, 98.1% of the strains were resistant to at least one antimicrobial agent and 63.5% of the isolates were classified as multidrug resistant (MDR). The top five virulence-associated genes were ssaQ (94.2%), avrA (92.3%), mgtC (92.3%), bcfC (87.2%) and siiD (84.6%). All of the Salmonella isolates harbored at least one virulence-associated gene, and 142 (91.0%) isolates co-harbored at least five virulence-associated genes. In addition, pulsed-field gel electrophoresis (PFGE) subtyping generated 41 PFGE patterns with a similarity index ranging from 33.8% to 99.1%. The majority of Salmonella isolates with same serovars or from same visit tended to cluster into identical pulsotypes, while a correlation among PFGE clusters, resistant profiles and virulotypes was not observed. The results revealed that Salmonella isolates from the duck slaughterhouse were not only genotype multiform, the majority of them were also multidrug resistant and co-carried multiple virulence-associated genes, which may pose potential risk to public health. Highlights: S. Indiana, S. Newlands and S. Newport were common serotypes. Virulotypes of same serotype varied significantly with different combinations. Correlation among PFGE clusters, resistance profiles and virulotypes was not observed. Introduced Salmonella was the major factor implicated in contamination at the duck slaughterhouse.